Ishmael - Quinn, Daniel (Bantam/Turner Book, 1995)
A man and a great ape conduct a series of philosophical conversations in a work that presents a new vision of evolution and humankind and asks the question: does the Earth belong to humans, or do humans belong to the Earth?